New Voltage Mode Universal Filters Using Only Two CDBAs. (11th February 2013) - Pathak, J. K.; Singh, A. K.; Senani, Raj
Abstract : Two new configurations for voltage mode universal filters (VMUFs) using only two current differencing buffered amplifiers (CDBAs) are proposed. Both of the new configurations can realize all the five standard types of the filters, namely, low pass (LP), high pass (HP), band pass (BP), band stop (BS), and all pass (AP), from the same topology. In contrast to previously known CDBA-based VMUFs, the new configurations do not need an additional active device for voltage inversion to realize all pass functions. The proposed configurations offer the tunability of the natural angular frequency( ω o ), quality factor( Q ), or the bandwidth (BW) through separate virtually grounded resistors. Moreover, both circuits have resistive input impedance (which can be made high) and a low output impedance to facilitate easy cascading without additional buffers. PSPICE simulation results, based upon commercially available AD844 ICs to implement the CDBA, are included which confirm the practical workability of the new VMUF configurations.